MOBILE APP FOR NURSING PROCESS IN A NEONATAL INTENSIVE CARE UNIT - Jhonathan Lucas Araujo (Texto & Contexto Enfermagem, 2019)
Purpose: to develop and validate a nursing process application in a neonatal intensive care unit. Method: a methodological study, conducted in a university hospital in southeastern Brazil from January 2017 to February 2018, divided into four stages: definition of requirements and elaboration of the conceptual model; generation of implementation and prototyping alternatives; testing and implementation. The app was developed based on Wanda Horta's Basic Human Needs and International Classification for Nursing Practice and following the User Centered Design method and the standards of the Brazilian Association of Software Engineering Technical Standards for IOS and Android platforms. The product was evaluated and validated by nurses for functional suitability, reliability, usability, performance efficiency, compatibility and safety. Results: the CuidarTech NeoProcesso de Enfermagemapp has screens that integrate the elements for history, diagnosis and nursing interventions. According to the judges' evaluation, it has functional adequacy, reliability, usability, performance efficiency, compatibility and safety. Conclusion: the app designed and validated by nurses is a computerized instrument that contains the stages of the nursing process: history, diagnoses and interventions, organized by Basic Human Needs and following the taxonomy of the International Classification for Nursing Practices. It relates information of newborns admitted to Neonatal Intensive Care Units and the nursing process, being able to provide quality, effectiveness, safety and personal satisfaction to the nurse's care.